Schistosoma haematobium infection status and its associated risk factors among pregnant women in Munyenge, South West Region, Cameroon following scale-up of communal piped water sources from 2014 to 2017: a cross-sectional study - Godlove Bunda Wepnje; Judith Kuoh Anchang-Kimbi; Vicky Daonyle Ndassi; Leopold Gustave Lehman; Helen Kuokuo Kimbi (BMC, 2019)
Abstract Background In 2014, a study in Munyenge revealed a high prevalence of urogenital schistosomiasis (UGS) among pregnant women. This study investigated he prevalence and risk factors of UGS in pregnancy following scale-up of piped water sources from 2014 to 2017. Secondly, we compared stream usage, stream contact behaviour, infection rate and intensity with the findings of 2014. Methods Consenting pregnant women reporting for antenatal care (ANC) in the different health facilities were enrolled consecutively between November 2016 and January 2018. Information on age, gravidity status, residence, marital status, educational level, occupation, household water source, frequency of contact with water and stream activities were obtained using a semi-structured questionnaire. Urine samples were examined for the presence of microhaematuria and S. haematobium ova using test strip and filtration/microscopy methods respectively. Data were analysed using univariate and multivariate regression analyses and relative risk reductions calculated. Results Of the 368 women enrolled, 22.3% (82) were diagnosed with UGS. Marital status (single) (aOR = 2.24, 95% CI: 1.04-4.79), primary - level of education (aOR = 2.0; 95% CI: 1.04-3.85) and domestic activity and bathing in the stream (aOR = 3.3; 95% CI: 1.83-6.01) increased risk of S. haematobium infection. Meanwhile, fewer visits (< 3 visits/week) to stream (aOR = 0.35, 95% CI = 0.17-0.74) reduced exposure to infection. Piped water usage was associated with reduced stream usage and eliminated the risk of infection among women who used safe water only. Compared with the findings of 2014, stream usage (RRR = 23 95% CI: 19-28), frequency (≥ 3 visits) (RRR = 69 95% CI: 59-77) and intensity of contact with water (RRR = 37 95% CI = 22-49) has reduced. Similarly, we observed a decrease in infection rate (RRR = 52, 95% CI = 40-62) and prevalence of heavy egg intensity (RRR = 71, 95% CI = 53-81). Conclusion Following increased piped water sources in Munyenge, S. haematobium infection has declined due to reduced stream contact. This has important implication in the control of UGS in pregnancy.